Medicinal herbs and plants in medieval medical practice (based on the Latin poem “De viribus herbarum” by Macer Floridus) - Petryshyn, Marta J.; Zahaiska, Halina M.; Liubimova, Oxana V.; Todoshchuk, Veronika H. (Wiadomości lekarskie. Monthly journal. Aluna Publishing House, Poland, 2022)
The aim of the study is to analyze the use of medicinal plants and herbs in the medieval medical practice. Materials and methods: The study is based on the Latin poem "De viribus herbarum" by the 11th century French physician Macer Floridus. Conclusions: Medicinal plants and herbs were successfully used to treat diseases of the gastrointestinal tract, spleen, hepatobiliary system, urinary and respiratory organs and were also applied in gynecology, dermatology, ophthalmology and dentistry.
Medicinal herbs and plants in medieval medical practice (based on the Latin poem “De viribus herbarum” by Macer Floridus)
Keywords: history of medicine, phytotherapy, Odo Magdunensis, herbal text